Clavadoce (Annelida: Phyllodocidae) from Australia - Wilson, Robin S.; Greaves, Elizabeth (Zootaxa, 2016)
The first records of the phyllodocid genus Clavadoce are provided from Australia, where the fifth species in the genus is now known: Clavadoce dorsolobata (Hartmann-Schröder, 1987) comb. nov. which is widely distributed in intertidal habitats in southeastern Australia. Clavadoce dorsolobata was described as Eumida (Sige) dorsolobata Hartmann-Schröder, 1987 and herein transferred to Clavadoce. Five species of Clavadoce are now known world wide, four of which are from different regions on the Pacific Ocean margin, while Clavadoce cristata is from the North Atlantic. The Australian species is the first record of Clavadoce for the southern hemisphere.